Real Estate in the Netherlands : A Taxonomy of Risks and Policy Challenges - Geis, Andre (IMF Working Papers; Working Paper, 2021)
Soaring real estate prices and valuations despite the economic downturn brought by the pandemic have focussed the attention of Dutch policymakers on potential macro-financial and socio-economic implications. In this context, our paper reviews the salient features of Dutch commercial and residential real estate markets with an eye to identify pertinent risks and challenges. While we find that the Dutch authorities have made considerable strides to strengthen real estate-related policies in recent years, some, and partly long-standing, issues remain, requiring additional efforts to bolster financial stability, address housing supply shortages and manage secular changes affecting property markets.